Status of lymphatic filariasis with progression of age and gender & eradication strategies: A survey among residents of Hardoi district of Uttar Pradesh, an endemic region of North India - Saeed, Mohd; Faisal, Syed Mohd; Ahmad, Irfan; Kausar, Mohd Adnan; Alam, Md Jahoor; Khan, Saif; Mustafa, Huma (Cellular and Molecular Biology, 2018)
Lymphatic filariasis (LF) is a chronic and debilitating disease that affects people in tropical and sub-tropical areas of Asia, Africa, and Western Pacific. It is one of the leading community health problems in some of the endemic districts in India including Hardoi district of Uttar Pradesh. The disease is caused by the parasites Wuchereria bancrofti (W. bancrofti), Brugia malayi (B. malayi) and Brugia timori (B. timori), transmitted by the vector Culex, Anopheles and other mosquitoes. This cross-sectional survey study was carried out in rural areas, where its inhabitants vary in socio-economic status, from low to middle-income class. 12 villages of Hardoi district, Uttar Pradesh, India were included. The aim was to see the impact of age and gender on various clinical forms of LF and in estimating its economic and social implications. 260 LF affected people in different parts of Hardoi district were surveyed. The results revealed that the Mass Drug Administration (MDA) coverage reached more than 90%. The overall Microfilaria rate had been reduced, however the prevalence of elephantiasis increased with the progression of age and was found to be highest among people of >70 years of age, regardless of their gender.